The Survey of educational facilities and present the kinds of program staff development of Nursing staff in hospitals of University of Medical sciences & health services in Tehran - Z Monjamed; F Nik Shekarnia; S Varaei; N Bahrani (Tehran University of Medical Sciences, 1999)
This study is a descriptive research in order to determine educational facilities and present the kinds of program staff development of nursing officeinhospitalsofuniversity of medical sciences and health services in Tehran, IRAN. The purpose of this research was determinated of the educational space (clossroom, library, Lecture and conference room), educational equipment, educational staff patterns, kinds of nursing staff development program and comparing between educational facilities and present the kinds of nursing development program of nursing office in three medical science university in Tehran. The units that participated in this research was 41 educational facilities and kinds of nursing staff development program of nursing office in three medical science university in Tehran (Tehran, Iran and shahid Beheshti) and no samphing was made. The tools was check list and Questionnarie. Each variable compared with educational standards of hospitals. (Standard 1100% excellent, desire was above 75% and undesired was under 75% and each 100 active bed haveing one educational supervisor).The finding indicated that scale confirmity with standard about educational space in three university was 50% (undesirable) and about educational equipment was 56% (undesirable) and about educational staffing pattern was 79% (desirable) and present kinds of nursing staff development was 56.5% (undesirable). The finding indicated that university medical of science Iran 66.5%, Shahid Beheshti 59.76% and Tehran 55.3% Scale confirmity with stundards have prossess.